Exploring healthcare staff narratives to gain an in-depth understanding of changing multidisciplinary team power dynamics during the COVID-19 pandemic - Lisa Rogers; Aoife De Brún; Eilish McAuliffe (BMC, 2023)
Abstract Background Multidisciplinary teams (MDTs) are integral to healthcare provision. However, healthcare has historically adopted a hierarchical power structure meaning some voices within the MDT have more influence than others. While power dynamics can influence interprofessional communication and care coordination, the field's understanding of these power structures during the COVID-19 pandemic is limited. Methods Adopting a narrative inquiry methodology, this research addresses this knowledge gap and provides an in-depth understanding of MDT power dynamics during COVID-19. Using semi-structured interviews (n = 35) and inductive thematic analysis, this research explores staff perspectives of changing power dynamics in MDTs during the pandemic response. Results An in-depth analysis generated three overarching themes: (1) Healthcare: a deeply embedded hierarchy reveals that while a hierarchical culture prevails within the Irish health system, staff perceptions of influence in MDTs and 'real' experiences of autonomy differ significantly. (2) Team characteristics: the influence of team structure on MDT power dynamics highlights the impact of organisational structures (e.g., staff rotations) and local processes (e.g., MDT meeting structure) on collaborative practice. (3) Ongoing effort to stimulate true collaboration underscores the importance of ongoing interprofessional education to support collaborative care. Conclusion By offering a greater understanding of MDT power dynamics throughout the COVID-19 pandemic, this research supports the development of more appropriate strategies to promote the provision of interprofessional care in practice.